2016
DOI: 10.1016/j.bbrc.2016.05.125
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic role of cytochrome P450 (CYP)1B1 in oxygen-mediated toxicity in pulmonary cells: A novel target for prevention of hyperoxic lung injury

Abstract: Supplemental oxygen, which is routinely administered to preterm infants with pulmonary insufficiency, contributes to bronchopulmonary dysplasia (BPD) in these infants. Hyperoxia also contributes to the development of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) in adults. The mechanisms of oxygen-mediated pulmonary toxicity are not completely understood. Recent studies have suggested an important role for cytochrome P450 (CYP)1A1/1A2 in the protection against hyperoxic lung injury. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Our initial study found that CYP1B1 may in fact contribute to hyperoxic toxicity. Cells overexpressing CYP1B1 showed increased hyperoxic toxicity in an MTT assay and cells in which CYP1B1 was knocked down showed decreased caspase 3/7 activity, a marker of apoptosis [56]. We have also found that Cyp1b1 −/− mice are less susceptible to hyperoxic lung injury, suggesting that CYP1B1, unlike CYP1A, contributes to hyperoxic toxicity (Veith et al, unpublished data).…”
Section: Role Of Cyp Enzymes In Ros Metabolism and Diseasesmentioning
confidence: 94%
“…Our initial study found that CYP1B1 may in fact contribute to hyperoxic toxicity. Cells overexpressing CYP1B1 showed increased hyperoxic toxicity in an MTT assay and cells in which CYP1B1 was knocked down showed decreased caspase 3/7 activity, a marker of apoptosis [56]. We have also found that Cyp1b1 −/− mice are less susceptible to hyperoxic lung injury, suggesting that CYP1B1, unlike CYP1A, contributes to hyperoxic toxicity (Veith et al, unpublished data).…”
Section: Role Of Cyp Enzymes In Ros Metabolism and Diseasesmentioning
confidence: 94%
“…Human cells overexpressing CYP1B1 were more susceptible to oxygen toxicity, while the use of CYP1B1-siRNA attenuated the toxic effect of hyperoxia. In immortalized lung endothelial cells derived from Cyp1b1-null and wild-type mice, Cyp1b1 expression promoted apoptosis induced by oxidative stress, while in cells derived from Cyp1b1-null mice, hyperoxia cytotoxicity was significantly diminished [31]. In studies in vivo, Cyp1b1−/− mice lacking the cytochrome P450 1B1 gene were less susceptible to hyperoxic lung injury than C57BL/6 wild type mice [32].…”
Section: Redox Homeostasismentioning
confidence: 95%
“…The role of CYP1B1 in hyperoxia cytotoxicity in human lung endothelial cells in vitro was studied [31]. Human cells overexpressing CYP1B1 were more susceptible to oxygen toxicity, while the use of CYP1B1-siRNA attenuated the toxic effect of hyperoxia.…”
Section: Redox Homeostasismentioning
confidence: 99%
“…As the level of oxidation reactions controls ROS production, changes in the activity of these enzymes as a result of various conditions can result in ROSmediated damage. As an example, enzyme CYP1B1 in pulmonary cells is associated with oxygenmediated pulmonary toxicity in cases of hyperoxia where its activity increases and ROS production rises (14). Enzyme CYP2E1, found in hepatocytes, shows an increase in activity after heavy alcohol consumption, leading to enhanced ROS production (15).…”
Section: Physiological Sources Of Rosmentioning
confidence: 99%